Means of expressing certain extremely large numbers
Conway chained arrow notation , created by mathematician John Horton Conway , is a means of expressing certain extremely large numbers .[ 1] It is simply a finite sequence of positive integers separated by rightward arrows, e.g.
2
→
3
→
4
→
5
→
6
{\displaystyle 2\to 3\to 4\to 5\to 6}
.
As with most combinatorial notations, the definition is recursive . In this case the notation eventually resolves to being the leftmost number raised to some (usually enormous) integer power.
Definition and overview [ edit ]
A "Conway chain" is defined as follows:
Any positive integer is a chain of length
1
{\displaystyle 1}
.
A chain of length n , followed by a right-arrow → and a positive integer, together form a chain of length
n
+
1
{\displaystyle n+1}
.
Any chain represents an integer, according to the six rules below. Two chains are said to be equivalent if they represent the same integer.
Let
a
,
b
,
c
{\displaystyle a,b,c}
denote positive integers and let
#
{\displaystyle \#}
denote the unchanged remainder of the chain. Then:
An empty chain (or a chain of length 0) is equal to
1
{\displaystyle 1}
The chain
a
{\displaystyle a}
represents the number
a
{\displaystyle a}
.
The chain
a
→
b
{\displaystyle a\rightarrow b}
represents the number
a
b
{\displaystyle a^{b}}
.
The chain
a
→
b
→
c
{\displaystyle a\rightarrow b\rightarrow c}
represents the number
a
↑
c
b
{\displaystyle a\uparrow ^{c}b}
(see Knuth's up-arrow notation )
The chains
#
→
1
{\displaystyle \#\rightarrow 1}
and
#
→
1
→
a
{\displaystyle \#\rightarrow 1\rightarrow a}
represent the same number as the chain
#
{\displaystyle \#}
Else, the chain
#
→
(
a
+
1
)
→
(
b
+
1
)
{\displaystyle \#\rightarrow (a+1)\rightarrow (b+1)}
represents the same number as the chain
#
→
(
#
→
a
→
(
b
+
1
)
)
→
b
{\displaystyle \#\rightarrow (\#\rightarrow a\rightarrow (b+1))\rightarrow b}
.
Let
X
,
Y
{\displaystyle X,Y}
denote sub-chains of length 1 or greater.
A chain evaluates to a perfect power of its first number
Therefore,
1
→
Y
{\displaystyle 1\to Y}
is equal to
1
{\displaystyle 1}
X
→
1
→
Y
{\displaystyle X\to 1\to Y}
is equivalent to
X
{\displaystyle X}
2
→
2
→
Y
{\displaystyle 2\to 2\to Y}
is equal to
4
{\displaystyle 4}
X
→
2
→
2
{\displaystyle X\to 2\to 2}
is equivalent to
X
→
(
X
)
{\displaystyle X\to (X)}
One must be careful to treat an arrow chain as a whole . Arrow chains do not describe the iterated application of a binary operator. Whereas chains of other infixed symbols (e.g. 3 + 4 + 5 + 6 + 7) can often be considered in fragments (e.g. (3 + 4) + 5 + (6 + 7)) without a change of meaning (see associativity ), or at least can be evaluated step by step in a prescribed order, e.g. 34567 from right to left, that is not so with Conway's arrow chains.
For example:
2
→
3
→
2
=
2
↑↑
3
=
2
2
2
=
2
4
=
16
{\displaystyle 2\rightarrow 3\rightarrow 2=2\uparrow \uparrow 3=2^{2^{2}}=2^{4}=16}
2
→
(
3
→
2
)
=
2
3
2
=
2
9
=
512
{\displaystyle 2\rightarrow (3\rightarrow 2)=2^{3^{2}}=2^{9}=512}
(
2
→
3
)
→
2
=
(
2
3
)
2
=
8
2
=
64
{\displaystyle (2\rightarrow 3)\rightarrow 2=(2^{3})^{2}=8^{2}=64}
The sixth definition rule is the core: A chain of 4 or more elements ending with 2 or higher becomes a chain of the same length with a (usually vastly) increased penultimate element. But its ultimate element is decremented, eventually permitting the fifth rule to shorten the chain. After, to paraphrase Knuth , "much detail", the chain is reduced to three elements and the fourth rule terminates the recursion.
Examples get quite complicated quickly. Here are some small examples:
n
{\displaystyle n}
=
n
{\displaystyle =n}
(By rule 2)
p
→
q
{\displaystyle p\to q}
=
p
q
{\displaystyle =p^{q}}
(By rule 3)
Thus,
3
→
4
=
3
4
=
81
{\displaystyle 3\to 4=3^{4}=81}
4
→
3
→
2
{\displaystyle 4\to 3\to 2}
=
4
↑↑
3
{\displaystyle =4\uparrow \uparrow 3}
(By rule 4)
=
4
↑
(
4
↑
4
)
{\displaystyle =4\uparrow (4\uparrow 4)}
=
4
↑
256
{\displaystyle =4\uparrow 256}
=
4
256
{\displaystyle =4^{256}}
=
13
,
407
,
807
,
929
,
942
,
597
,
099
,
574
,
024
,
998
,
205
,
846
,
127
,
479
,
365
,
820
,
592
,
393
,
377
,
723
,
561
,
443
,
721
,
764
,
030
,
073
,
{\displaystyle =13,407,807,929,942,597,099,574,024,998,205,846,127,479,365,820,592,393,377,723,561,443,721,764,030,073,}
546
,
976
,
801
,
874
,
298
,
166
,
903
,
427
,
690
,
031
,
858
,
186
,
486
,
050
,
853
,
753
,
882
,
811
,
946
,
569
,
946
,
433
,
649
,
006
,
084
,
096
{\displaystyle 546,976,801,874,298,166,903,427,690,031,858,186,486,050,853,753,882,811,946,569,946,433,649,006,084,096}
≈
1.34
∗
10
154
{\displaystyle \approx 1.34*10^{154}}
2
→
2
→
a
{\displaystyle 2\to 2\to a}
=
2
[
↑
a
]
2
{\displaystyle =2[\uparrow ^{a}]2}
(By rule 4)
=
4
{\displaystyle =4}
(see Knuth's up arrow notation )
2
→
4
→
3
{\displaystyle 2\to 4\to 3}
=
2
↑↑↑
4
{\displaystyle =2\uparrow \uparrow \uparrow 4}
(By rule 4)
=
2
↑↑
2
↑↑
2
↑↑
2
{\displaystyle =2\uparrow \uparrow 2\uparrow \uparrow 2\uparrow \uparrow 2}
=
2
↑↑
2
↑↑
4
{\displaystyle =2\uparrow \uparrow 2\uparrow \uparrow 4}
=
2
↑↑
2
↑
2
↑
2
↑
2
{\displaystyle =2\uparrow \uparrow 2\uparrow 2\uparrow 2\uparrow 2}
=
2
↑↑
2
↑
2
↑
4
{\displaystyle =2\uparrow \uparrow 2\uparrow 2\uparrow 4}
=
2
↑↑
2
↑
16
{\displaystyle =2\uparrow \uparrow 2\uparrow 16}
=
2
↑↑
65536
{\displaystyle =2\uparrow \uparrow 65536}
=
65536
2
{\displaystyle ={^{65536}2}}
(see tetration )
2
→
3
→
2
→
2
{\displaystyle 2\to 3\to 2\to 2}
=
2
→
3
→
(
2
→
3
)
→
1
{\displaystyle =2\to 3\to (2\to 3)\to 1}
(By rule 6)
=
2
→
3
→
8
→
1
{\displaystyle =2\to 3\to 8\to 1}
(By rule 3)
=
2
→
3
→
8
{\displaystyle =2\to 3\to 8}
(By rule 5)
=
2
→
(
2
→
2
→
8
)
→
7
{\displaystyle =2\to (2\to 2\to 8)\to 7}
(By rule 6)
=
2
→
4
→
7
{\displaystyle =2\to 4\to 7}
(By rule 6)
=
2
↑↑↑↑↑↑↑
4
{\displaystyle =2\uparrow \uparrow \uparrow \uparrow \uparrow \uparrow \uparrow 4}
(By rule 4)
= much larger than previous number
3
→
2
→
2
→
2
{\displaystyle 3\to 2\to 2\to 2}
=
3
→
2
→
(
3
→
2
)
→
1
{\displaystyle =3\to 2\to (3\to 2)\to 1}
(By rule 6)
=
3
→
2
→
9
→
1
{\displaystyle =3\to 2\to 9\to 1}
(By rule 3)
=
3
→
2
→
9
{\displaystyle =3\to 2\to 9}
(By rule 5)
=
3
→
3
→
8
{\displaystyle =3\to 3\to 8}
(By rule 6)
=
3
↑↑↑↑↑↑↑↑
3
{\displaystyle =3\uparrow \uparrow \uparrow \uparrow \uparrow \uparrow \uparrow \uparrow 3}
(By rule 4)
= much, much larger than previous number
Systematic examples [ edit ]
The simplest cases with four terms (containing no integers less than 2) are:
a
→
b
→
2
→
2
{\displaystyle a\to b\to 2\to 2}
=
a
→
b
→
2
→
(
1
+
1
)
{\displaystyle =a\to b\to 2\to (1+1)}
=
a
→
b
→
(
a
→
b
)
→
1
{\displaystyle =a\to b\to (a\to b)\to 1}
=
a
→
b
→
a
b
{\displaystyle =a\to b\to a^{b}}
=
a
[
a
b
+
2
]
b
{\displaystyle =a[a^{b}+2]b}
(equivalent to the last-mentioned property)
a
→
b
→
3
→
2
{\displaystyle a\to b\to 3\to 2}
=
a
→
b
→
3
→
(
1
+
1
)
{\displaystyle =a\to b\to 3\to (1+1)}
=
a
→
b
→
(
a
→
b
→
(
a
→
b
)
→
1
)
→
1
{\displaystyle =a\to b\to (a\to b\to (a\to b)\to 1)\to 1}
=
a
→
b
→
(
a
→
b
→
a
b
)
{\displaystyle =a\to b\to (a\to b\to a^{b})}
=
a
[
a
→
b
→
2
→
2
+
2
]
b
{\displaystyle =a[a\to b\to 2\to 2+2]b}
a
→
b
→
4
→
2
{\displaystyle a\to b\to 4\to 2}
=
a
→
b
→
(
a
→
b
→
(
a
→
b
→
a
b
)
)
{\displaystyle =a\to b\to (a\to b\to (a\to b\to a^{b}))}
=
a
[
a
→
b
→
3
→
2
+
2
]
b
{\displaystyle =a[a\to b\to 3\to 2+2]b}
We can see a pattern here. If, for any chain
X
{\displaystyle X}
, we let
f
(
p
)
=
X
→
p
{\displaystyle f(p)=X\to p}
then
X
→
p
→
2
=
f
p
(
1
)
{\displaystyle X\to p\to 2=f^{p}(1)}
(see functional powers ).
Applying this with
X
=
a
→
b
{\displaystyle X=a\to b}
, then
f
(
p
)
=
a
[
p
+
2
]
b
{\displaystyle f(p)=a[p+2]b}
and
a
→
b
→
p
→
2
=
a
[
a
→
b
→
(
p
−
1
)
→
2
+
2
]
b
=
f
p
(
1
)
{\displaystyle a\to b\to p\to 2=a[a\to b\to (p-1)\to 2+2]b=f^{p}(1)}
Thus, for example,
10
→
6
→
3
→
2
=
10
[
10
[
1000002
]
6
+
2
]
6
{\displaystyle 10\to 6\to 3\to 2=10[10[1000002]6+2]6}
.
Moving on:
a
→
b
→
2
→
3
{\displaystyle a\to b\to 2\to 3}
=
a
→
b
→
2
→
(
2
+
1
)
{\displaystyle =a\to b\to 2\to (2+1)}
=
a
→
b
→
(
a
→
b
)
→
2
{\displaystyle =a\to b\to (a\to b)\to 2}
=
a
→
b
→
a
b
→
2
{\displaystyle =a\to b\to a^{b}\to 2}
=
f
a
b
(
1
)
{\displaystyle =f^{a^{b}}(1)}
Again we can generalize. When we write
g
q
(
p
)
=
X
→
p
→
q
{\displaystyle g_{q}(p)=X\to p\to q}
we have
X
→
p
→
q
+
1
=
g
q
p
(
1
)
{\displaystyle X\to p\to q+1=g_{q}^{p}(1)}
, that is,
g
q
+
1
(
p
)
=
g
q
p
(
1
)
{\displaystyle g_{q+1}(p)=g_{q}^{p}(1)}
. In the case above,
g
2
(
p
)
=
a
→
b
→
p
→
2
=
f
p
(
1
)
{\displaystyle g_{2}(p)=a\to b\to p\to 2=f^{p}(1)}
and
g
3
(
p
)
=
g
2
p
(
1
)
{\displaystyle g_{3}(p)=g_{2}^{p}(1)}
, so
a
→
b
→
2
→
3
=
g
3
(
2
)
=
g
2
2
(
1
)
=
g
2
(
g
2
(
1
)
)
=
f
f
(
1
)
(
1
)
=
f
a
b
(
1
)
{\displaystyle a\to b\to 2\to 3=g_{3}(2)=g_{2}^{2}(1)=g_{2}(g_{2}(1))=f^{f(1)}(1)=f^{a^{b}}(1)}
The Ackermann function can be expressed using Conway chained arrow notation:
A
(
m
,
n
)
=
(
2
→
(
n
+
3
)
→
(
m
−
2
)
)
−
3
{\displaystyle A(m,n)=(2\to (n+3)\to (m-2))-3}
for
m
≥
3
{\displaystyle m\geq 3}
(Since
A
(
m
,
n
)
=
2
[
m
]
(
n
+
3
)
−
3
{\displaystyle A(m,n)=2[m](n+3)-3}
in hyperoperation )
hence
2
→
n
→
m
=
A
(
m
+
2
,
n
−
3
)
+
3
{\displaystyle 2\to n\to m=A(m+2,n-3)+3}
for
n
>
2
{\displaystyle n>2}
(
n
=
1
{\displaystyle n=1}
and
n
=
2
{\displaystyle n=2}
would correspond with
A
(
m
,
−
2
)
=
−
1
{\displaystyle A(m,-2)=-1}
and
A
(
m
,
−
1
)
=
1
{\displaystyle A(m,-1)=1}
, which could logically be added).
Graham's number cannot be expressed in Conway chained arrow notation, but it is bounded by the following:
3
→
3
→
64
→
2
<
G
<
3
→
3
→
65
→
2
{\displaystyle 3\rightarrow 3\rightarrow 64\rightarrow 2<G<3\rightarrow 3\rightarrow 65\rightarrow 2}
Proof: We first define the intermediate function
f
(
n
)
=
3
→
3
→
n
=
3
↑↑
⋯
↑
⏟
3
n arrows
{\displaystyle f(n)=3\rightarrow 3\rightarrow n={\begin{matrix}3\underbrace {\uparrow \uparrow \cdots \uparrow } 3\\{\text{n arrows}}\end{matrix}}}
, which can be used to define Graham's number as
G
=
f
64
(
4
)
{\displaystyle G=f^{64}(4)}
. (The superscript 64 denotes a functional power .)
By applying rule 2 and rule 4 backwards, we simplify:
f
64
(
1
)
{\displaystyle f^{64}(1)}
=
3
→
3
→
(
3
→
3
→
(
⋯
(
3
→
3
→
(
3
→
3
→
1
)
)
⋯
)
)
{\displaystyle =3\rightarrow 3\rightarrow (3\rightarrow 3\rightarrow (\cdots (3\rightarrow 3\rightarrow (3\rightarrow 3\rightarrow 1))\cdots ))}
(with 64
3
→
3
{\displaystyle 3\rightarrow 3}
's)
=
3
→
3
→
(
3
→
3
→
(
⋯
(
3
→
3
→
(
3
→
3
)
→
1
)
⋯
)
→
1
)
→
1
{\displaystyle =3\rightarrow 3\rightarrow (3\rightarrow 3\rightarrow (\cdots (3\rightarrow 3\rightarrow (3\rightarrow 3)\rightarrow 1)\cdots )\rightarrow 1)\rightarrow 1}
=
3
→
3
→
64
→
2
;
{\displaystyle =3\rightarrow 3\rightarrow 64\rightarrow 2;}
=
3
↑↑
⋯
⋯
⋯
⋅
↑
⏟
3
3
↑↑
⋯
⋯
⋯
↑
⏟
3
⋮
⏟
3
↑↑
⋯
⋅
↑
⏟
3
3
↑
3
}
64 layers
{\displaystyle \left.{\begin{matrix}=&3\underbrace {\uparrow \uparrow \cdots \cdots \cdots \cdot \uparrow } 3\\&3\underbrace {\uparrow \uparrow \cdots \cdots \cdots \uparrow } 3\\&\underbrace {\qquad \;\;\vdots \qquad \;\;} \\&3\underbrace {\uparrow \uparrow \cdots \cdot \uparrow } 3\\&3\uparrow 3\end{matrix}}\right\}{\text{64 layers}}}
f
64
(
4
)
=
G
;
{\displaystyle f^{64}(4)=G;}
=
3
→
3
→
(
3
→
3
→
(
⋯
(
3
→
3
→
(
3
→
3
→
4
)
)
⋯
)
)
{\displaystyle =3\rightarrow 3\rightarrow (3\rightarrow 3\rightarrow (\cdots (3\rightarrow 3\rightarrow (3\rightarrow 3\rightarrow 4))\cdots ))}
(with 64
3
→
3
{\displaystyle 3\rightarrow 3}
's)
=
3
↑↑
⋯
⋯
⋯
⋅
↑
⏟
3
3
↑↑
⋯
⋯
⋯
↑
⏟
3
⋮
⏟
3
↑↑
⋯
⋅
↑
⏟
3
3
↑↑↑↑
3
}
64 layers
{\displaystyle \left.{\begin{matrix}=&3\underbrace {\uparrow \uparrow \cdots \cdots \cdots \cdot \uparrow } 3\\&3\underbrace {\uparrow \uparrow \cdots \cdots \cdots \uparrow } 3\\&\underbrace {\qquad \;\;\vdots \qquad \;\;} \\&3\underbrace {\uparrow \uparrow \cdots \cdot \uparrow } 3\\&3\uparrow \uparrow \uparrow \uparrow 3\end{matrix}}\right\}{\text{64 layers}}}
f
64
(
27
)
{\displaystyle f^{64}(27)}
=
3
→
3
→
(
3
→
3
→
(
⋯
(
3
→
3
→
(
3
→
3
→
27
)
)
⋯
)
)
{\displaystyle =3\rightarrow 3\rightarrow (3\rightarrow 3\rightarrow (\cdots (3\rightarrow 3\rightarrow (3\rightarrow 3\rightarrow 27))\cdots ))}
(with 64
3
→
3
{\displaystyle 3\rightarrow 3}
's)
=
3
→
3
→
(
3
→
3
→
(
⋯
(
3
→
3
→
(
3
→
3
→
(
3
→
3
)
)
)
⋯
)
)
{\displaystyle =3\rightarrow 3\rightarrow (3\rightarrow 3\rightarrow (\cdots (3\rightarrow 3\rightarrow (3\rightarrow 3\rightarrow (3\rightarrow 3)))\cdots ))}
(with 65
3
→
3
{\displaystyle 3\rightarrow 3}
's)
=
3
→
3
→
65
→
2
{\displaystyle =3\rightarrow 3\rightarrow 65\rightarrow 2}
(computing as above).
=
f
65
(
1
)
{\displaystyle =f^{65}(1)}
=
3
↑↑
⋯
⋯
⋯
⋅
↑
⏟
3
3
↑↑
⋯
⋯
⋯
↑
⏟
3
⋮
⏟
3
↑↑
⋯
⋅
↑
⏟
3
3
↑
3
}
65 layers
{\displaystyle \left.{\begin{matrix}=&3\underbrace {\uparrow \uparrow \cdots \cdots \cdots \cdot \uparrow } 3\\&3\underbrace {\uparrow \uparrow \cdots \cdots \cdots \uparrow } 3\\&\underbrace {\qquad \;\;\vdots \qquad \;\;} \\&3\underbrace {\uparrow \uparrow \cdots \cdot \uparrow } 3\\&3\uparrow 3\end{matrix}}\right\}{\text{65 layers}}}
Since f is strictly increasing ,
f
64
(
1
)
<
f
64
(
4
)
<
f
64
(
27
)
{\displaystyle f^{64}(1)<f^{64}(4)<f^{64}(27)}
which is the given inequality.
With chained arrows, it is very easy to specify a number much greater than Graham's number, for example,
3
→
3
→
3
→
3
{\displaystyle 3\rightarrow 3\rightarrow 3\rightarrow 3}
.
3
→
3
→
3
→
3
{\displaystyle 3\rightarrow 3\rightarrow 3\rightarrow 3}
=
3
→
3
→
(
3
→
3
→
27
→
2
)
→
2
{\displaystyle =3\rightarrow 3\rightarrow (3\rightarrow 3\rightarrow 27\rightarrow 2)\rightarrow 2\,}
=
f
3
→
3
→
27
→
2
(
1
)
{\displaystyle =f^{3\rightarrow 3\rightarrow 27\rightarrow 2}(1)}
=
f
f
27
(
1
)
(
1
)
{\displaystyle =f^{f^{27}(1)}(1)}
=
3
↑↑
⋯
⋯
⋯
⋅
⋅
↑
⏟
3
3
↑↑
⋯
⋯
⋯
⋅
↑
⏟
3
3
↑↑
⋯
⋯
⋯
↑
⏟
3
⋮
⏟
3
↑↑
⋯
⋅
↑
⏟
3
3
↑
3
}
3
↑↑
⋯
⋯
⋯
⋅
↑
⏟
3
3
↑↑
⋯
⋯
⋯
↑
⏟
3
⋮
⏟
3
↑↑
⋯
⋅
↑
⏟
3
3
↑
3
}
27
{\displaystyle \left.{\begin{matrix}=&3\underbrace {\uparrow \uparrow \cdots \cdots \cdots \cdot \cdot \uparrow } 3\\&3\underbrace {\uparrow \uparrow \cdots \cdots \cdots \cdot \uparrow } 3\\&3\underbrace {\uparrow \uparrow \cdots \cdots \cdots \uparrow } 3\\&\underbrace {\qquad \;\;\vdots \qquad \;\;} \\&3\underbrace {\uparrow \uparrow \cdots \cdot \uparrow } 3\\&3\uparrow 3\end{matrix}}\right\}\left.{\begin{matrix}3\underbrace {\uparrow \uparrow \cdots \cdots \cdots \cdot \uparrow } 3\\3\underbrace {\uparrow \uparrow \cdots \cdots \cdots \uparrow } 3\\\underbrace {\qquad \;\;\vdots \qquad \;\;} \\3\underbrace {\uparrow \uparrow \cdots \cdot \uparrow } 3\\3\uparrow 3\end{matrix}}\right\}\ 27}
which is much greater than Graham's number, because the number
3
→
3
→
27
→
2
{\displaystyle 3\rightarrow 3\rightarrow 27\rightarrow 2}
=
f
27
(
1
)
{\displaystyle =f^{27}(1)}
is much greater than
65
{\displaystyle 65}
.
Conway and Guy created a simple, single-argument function that diagonalizes over the entire notation, defined as:
c
g
(
n
)
=
n
→
n
→
n
→
⋯
→
n
→
n
→
n
⏟
n
{\displaystyle cg(n)=\underbrace {n\rightarrow n\rightarrow n\rightarrow \dots \rightarrow n\rightarrow n\rightarrow n} _{n}}
meaning the sequence is:
c
g
(
1
)
=
1
{\displaystyle cg(1)=1}
c
g
(
2
)
=
2
→
2
=
2
2
=
4
{\displaystyle cg(2)=2\to 2=2^{2}=4}
c
g
(
3
)
=
3
→
3
→
3
=
3
↑↑↑
3
{\displaystyle cg(3)=3\to 3\to 3=3\uparrow \uparrow \uparrow 3}
c
g
(
4
)
=
4
→
4
→
4
→
4
{\displaystyle cg(4)=4\to 4\to 4\to 4}
c
g
(
5
)
=
5
→
5
→
5
→
5
→
5
{\displaystyle cg(5)=5\to 5\to 5\to 5\to 5}
...
This function, as one might expect, grows extraordinarily fast.
Extension by Peter Hurford [ edit ]
Peter Hurford, a web developer and statistician, has defined an extension to this notation:
a
→
b
c
=
a
→
b
−
1
a
→
b
−
1
a
→
b
−
1
⋯
→
b
−
1
a
→
b
−
1
a
→
b
−
1
a
⏟
c
arrows
{\displaystyle a\rightarrow _{b}c=\underbrace {a\rightarrow _{b-1}a\rightarrow _{b-1}a\rightarrow _{b-1}\dots \rightarrow _{b-1}a\rightarrow _{b-1}a\rightarrow _{b-1}a} _{c{\text{ arrows}}}}
a
→
1
b
=
a
→
b
{\displaystyle a\rightarrow _{1}b=a\rightarrow b}
All normal rules are unchanged otherwise.
a
→
2
(
a
−
1
)
{\displaystyle a\rightarrow _{2}(a-1)}
is already equal to the aforementioned
c
g
(
a
)
{\displaystyle cg(a)}
, and the function
f
(
n
)
=
n
→
n
n
{\displaystyle f(n)=n\rightarrow _{n}n}
is much faster growing than Conway and Guy's
c
g
(
n
)
{\displaystyle cg(n)}
.
Note that expressions like
a
→
b
c
→
d
e
{\displaystyle a\rightarrow _{b}c\rightarrow _{d}e}
are illegal if
b
{\displaystyle b}
and
d
{\displaystyle d}
are different numbers; a chain must have only one type of right-arrow.
However, if we modify this slightly such that:
a
→
b
c
→
d
e
=
a
→
b
c
→
d
−
1
c
→
d
−
1
c
→
d
−
1
⋯
→
d
−
1
c
→
d
−
1
c
→
d
−
1
c
⏟
e
arrows
{\displaystyle a\rightarrow _{b}c\rightarrow _{d}e=a\rightarrow _{b}\underbrace {c\rightarrow _{d-1}c\rightarrow _{d-1}c\rightarrow _{d-1}\dots \rightarrow _{d-1}c\rightarrow _{d-1}c\rightarrow _{d-1}c} _{e{\text{ arrows}}}}
then not only does
a
→
b
c
→
d
e
{\displaystyle a\rightarrow _{b}c\rightarrow _{d}e}
become legal, but the notation as a whole becomes much stronger.[ 2]
Primary Inverse for left argumentInverse for right argument Related articles
Examples in numerical order Expression methods
Related articles (alphabetical order)